Phosphine oxy group modified carbon felt adsorbing electrode material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611094377.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-23
AI Technical Summary
电极材料的制备绿色安全性仍有待提升
[0049](1)本发明提供的膦氧基修饰碳毡吸附电极材料相较于现有的吸附剂材料而言,用水作为解吸剂,而不是高浓度酸,解吸方式更加环保,避免吸附材料的破坏,循环性能更为优越。在较优条件下,组装于电容去离子器件中可以完成100次吸附-解吸循环,吸附率始终保持在89%以上。此外,外加电场形成的范德华力也会明显提升反应速率,可在3h和2.5h内分别达到针对铟和镓的吸附平衡;
Smart Images

Figure CN122960013A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic waste treatment and disposal technology, and in particular to a phosphoxy-modified carbon felt adsorption electrode material, its preparation method, and its application. Background Technology
[0002] Copper indium gallium selenide (CIGS, chemical formula CuInGaSe2) photovoltaic modules possess advantages such as being lightweight, thin, flexible, and performing well in low-light conditions, making them highly promising for applications in aerospace and building-integrated photovoltaics (BIPV). Their installed capacity is steadily increasing. The key components of CIGS photovoltaic modules are the rare metals indium and gallium, which are scarce and dispersed, resulting in low global supply. However, their unique properties lead to widespread applications in low-carbon technologies such as solar cells, electronic semiconductors, and radio, driving rapidly increasing demand. Therefore, separating and recovering indium and gallium from waste CIGS photovoltaic modules is crucial for alleviating supply shortages.
[0003] Currently, hydrometallurgical processes, including precipitation, extraction, adsorption, and electrochemistry, are the main methods for indium gallium (IGa) recovery. However, single methods often have inherent limitations. Therefore, capacitive deionization technology, which combines adsorbents with electrochemical driving forces, has emerged. Based on the electric double-layer theory, this technology works by applying a small electric field (≤1.2 V) between a pair of parallel electrodes to polarize them. Ions with opposite charges in the solution are attracted to the polarized electrodes under the influence of Coulomb forces and accumulate, thus achieving adsorption. When the applied voltage stops or reverses, the charged ions on the electrodes are released, completing desorption and electrode regeneration. In the current field of IGa recovery, capacitive deionization technology is in its early stages of application but has enormous potential.
[0004] Capacitive deionization is applied in metal ion recovery. An external electric field can accelerate the adsorption and desorption reaction rates, simplifying reaction steps and achieving in-situ green desorption. The adsorption capacity, selectivity, and recyclability of the electrode material significantly affect the recovery rate and purity of metal ions. A common method for preparing electrode materials involves mixing active materials with conductive agents (such as carbon black) and binders (such as polyvinylidene fluoride) and then casting the mixture into a current collector. However, organic binders not only pose certain environmental risks but also easily lead to reduced electrode stability and conductivity. Therefore, the greenness and recyclability of electrode material preparation still need improvement. CN202310132480 discloses a method for treating heavy metal wastewater using zinc-modified biochar electrode materials. This electrode material is prepared by calcining and acid washing zinc-modified biochar using zinc chloride as a modifier. The biochar is then mixed with a binder and solvent to form an electrode slurry. This slurry is then mixed with carbon felt and subjected to ultrasonication and drying to obtain a carbon felt electrode material. Introducing biochar with high specific surface area and abundant pore structure significantly improves electrode performance, but the use of binders still needs improvement.
[0005] CN202510410715 discloses a grapefruit peel activated carbon for capacitor deionization, its preparation method, and its application. This activated carbon is prepared by hydrothermal carbonization and high-temperature activation of waste grapefruit peel. Its numerous micropores and mesopores provide abundant active sites and reaction space for ion storage, diffusion, and transport, thereby improving electrode performance. However, this activated carbon needs to be mixed with an organic binder (polyvinylidene fluoride) and organic solvents (ethanol, acetone, and N-methylpyrrolidone) to form a slurry before it can be coated onto a current collector to form an electrode. Therefore, the greenness, safety, and economy of this electrode material need further improvement.
[0006] In summary, the adsorption capacity, selectivity, and stability of adsorption electrode materials have a significant impact on the performance of capacitive deionization devices in the field of metal ion separation and recovery. The green and safe preparation of electrode materials still needs improvement. Therefore, providing a novel adsorption electrode material that is green, safe, and exhibits excellent adsorption performance is of great significance. Summary of the Invention
[0007] In view of the problems existing in the prior art, the present invention provides a phosphoxy-modified carbon felt adsorption electrode material, its preparation method and application. The adsorption electrode material provided by the present invention has excellent adsorption performance and material stability, and can be used for the efficient separation and recovery of rare metals indium and gallium in waste photovoltaic modules. The preparation method is carried out in a normal temperature and pressure environment throughout the process, without the use of any binders or other toxic organic reagents. It is simple to operate, low in cost, green and safe.
[0008] To achieve this objective, the present invention adopts the following technical solution:
[0009] In a first aspect, the present invention provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material, the method comprising the following steps:
[0010] (1) Activated carbon, dopamine hydrochloride, phosphine-containing substrate and tris(hydroxymethyl)aminomethane hydrochloride are dispersed in a solvent and the pH is adjusted to alkaline to obtain a mixed dispersion;
[0011] (2) Immerse the carbon felt in the mixed dispersion obtained in step (1), and after the reaction is completed, obtain the phosphoxy-modified carbon felt adsorption electrode material.
[0012] In this invention, the main reaction principle is the synergistic action of dopamine self-polymerization and Artherton-Todd reaction: on the one hand, the polydopamine layer generated by the dopamine self-polymerization reaction has adhesive properties, which can uniformly coat the surface of carbon felt fibers and bind and fix active substances such as activated carbon in the mixed dispersion to the carbon felt surface, thereby forming a functional coating without the use of binders; on the other hand, the abundant hydroxyl groups on the surface of the polydopamine layer will undergo Artherton-Todd reaction with phosphine-containing substrates to achieve covalent grafting of phosphoxy groups. Compared with traditional electrode preparation methods, the material preparation method provided by this invention is carried out in a normal temperature and pressure environment throughout the process and does not use any toxic organic reagents, including binders, which has significant advantages in terms of economy, greenness, and safety.
[0013] This invention incorporates activated carbon into the functional coating. Activated carbon possesses a well-developed microporous and mesoporous structure. Compared to carbon felt with a smaller specific surface area, the large specific surface area and pores of activated carbon allow it to load more phosphoxy functional groups, thereby enhancing the adsorption capacity of these functional groups for rare metals. The carbon felt of this invention is ultrasonically and water-washed before use, and then cut to the required size; specific dimensions are not limited herein.
[0014] After the reaction of this invention is completed, solid-liquid separation and drying are performed. The drying temperature is 40-50℃, for example, 40℃, 42℃, 44℃, 46℃, 48℃ or 50℃, etc., and the drying time is 3-10h, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc., to obtain phosphoxy-modified carbon felt adsorption electrode material.
[0015] As a preferred technical solution of the present invention, the particle size range of the activated carbon is 60-850μm, for example, it can be 60μm, 100μm, 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm or 850μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0016] Preferably, the BJH desorption pore size of the activated carbon is 2-50 nm, for example, it can be 2 nm, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0017] Preferably, the activated carbon has a BET specific surface area of 1000-1800 m². 2 / g, for example, could be 1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g, 1400m2 / g, 1500m 2 / g, 1600m 2 / g、1700m 2 / g or 1800m 2 / g, etc., but not limited to the listed values, other unlisted values within the range also apply.
[0018] As a preferred embodiment of the present invention, the phosphine-containing substrate includes any one or a combination of at least two of diethyl phosphite, diisopropyl phosphite, phenylphosphine acid, ethyl phenylphosphine, or dimethylphosphine oxide.
[0019] In this invention, the phosphine-containing substrate is a phosphine-containing substrate capable of undergoing the Atherton-Todd reaction, and is divided into three categories according to the different grafting structures of phosphine atoms, including: (i) O,O-dialkylphosphonates, (ii) hypophosphite and (iii) dialkylphosphine oxides; further, the representative organic compounds of (i) are preferably diethyl phosphite and diisopropyl phosphite, the representative organic compounds of (ii) are preferably phenylphosphine acid and ethyl phenylphosphine, and the representative organic compounds of (iii) are preferably dimethylphosphine oxide.
[0020] As a preferred technical solution of the present invention, the solvent in step (1) includes water.
[0021] As a preferred embodiment of the present invention, the molar ratio of dopamine hydrochloride, phosphine-containing substrate, tris(hydroxymethyl)aminomethane hydrochloride, and water is (0.1-1):(1-10):(0.1-1):300, for example, it can be 0.1:1:0.1:300, 1:10:1:300, 0.1:10:0.1:300, 1:1:0.1:300, or 0.5:3:0.6:300, etc., but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0022] The present invention controls the molar ratio of dopamine hydrochloride, phosphine-containing substrate, tris(hydroxymethyl)aminomethane hydrochloride and water within the above range, which can further adjust the thickness and adhesion of the functional coating, and improve the phosphooxy grafting density while tightly modifying and fixing it to the carbon felt.
[0023] Preferably, the ratio of dopamine hydrochloride to activated carbon is (0.1-1) mol: (100-1000) g, for example, it can be 0.1 mol: 100 g, 1 mol: 1000 g, 1 mol: 100 g, 0.1 mol: 1000 g or 0.5 mol: 500 g, etc., but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0024] Preferably, the solid-liquid ratio of the carbon felt to the mixed dispersion in step (2) is (0.2-1):1g / mL, for example, it can be 0.2:1g / mL, 0.4:1g / mL, 0.6:1g / mL, 0.8:1g / mL or 1:1g / mL, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0025] The present invention controls the solid-liquid ratio of the carbon felt and the mixed dispersion within the above-mentioned range, which can regulate the specific surface area and pore structure of the adsorption electrode material, thereby improving the electrochemical performance such as ion transport rate, and thus improving the adsorption performance.
[0026] As a preferred technical solution of the present invention, the dispersion process in step (1) includes stirring.
[0027] Preferably, the stirring time is 1-2 hours, for example, it can be 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours or 2 hours, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0028] Preferably, the stirring speed is 50-200 r / min, for example, it can be 50 r / min, 80 r / min, 110 r / min, 140 r / min, 170 r / min or 200 r / min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0029] Preferably, the pH adjustment includes using potassium hydroxide and / or sodium hydroxide.
[0030] Preferably, the pH is adjusted to 8-9, for example, 8 or 9, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0031] As a preferred technical solution of the present invention, the reaction time in step (2) is 3-10h, for example, it can be 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc., but is not limited to the listed values. Other unlisted values within the range are also applicable, preferably 3-5h.
[0032] Preferably, the reaction temperature in step (2) is 20-30℃, for example, it can be 20℃, 22℃, 24℃, 26℃, 28℃ or 30℃, etc., but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0033] In a second aspect, the present invention provides a phosphoxy-modified carbon felt adsorption electrode material, which is prepared by the preparation method described in the first aspect.
[0034] The phosphoxy-modified carbon felt adsorption electrode material includes a carbon felt and a functional coating wrapped on the carbon felt.
[0035] The functional coating is grafted with phosphoxy functional groups.
[0036] The adsorption electrode material provided by this invention is prepared entirely in a normal temperature and pressure environment, without using any toxic organic reagents, and has excellent economy, greenness and safety; the surface of the prepared material achieves tight bonding between activated carbon and phosphooxy groups through a polydopamine layer, which significantly improves the adsorption performance of the electrode material.
[0037] Thirdly, the present invention provides an application of the phosphoxy-modified carbon felt adsorption electrode material as described in the second aspect, wherein the phosphoxy-modified carbon felt adsorption electrode material is used to assemble a capacitor deionization device, wherein the capacitor deionization device can selectively separate and recover rare metal elements in a solution.
[0038] The solution includes an acidic leachate from copper indium gallium selenide (CIGS) photovoltaic modules;
[0039] The phosphoxy-modified carbon felt adsorption electrode material provided by this invention can be used to recycle electronic waste, such as in the acidic leachate of waste copper indium gallium selenide photovoltaic modules. It can separate and recover indium and gallium from waste photovoltaic modules, alleviate the shortage of indium and gallium, and promote the sustainable development of the photovoltaic industry.
[0040] The rare metal elements include indium and / or gallium.
[0041] The electrode material prepared in this invention can be assembled into a capacitor deionization device, which can conveniently and efficiently separate and recover rare metals gallium and indium from mixed solutions containing multiple metal ions, effectively avoiding the drawbacks of traditional adsorption methods that require the use of acidic solutions to desorb metal ions and have cumbersome adsorption-desorption steps.
[0042] As a preferred embodiment of the present invention, the separation and recovery of rare metal elements in the solution includes the following steps:
[0043] (1) After disassembling and crushing copper indium gallium selenide photovoltaic modules, they are leached with nitric acid to obtain an acidic leachate containing rare metals gallium and indium.
[0044] (2) Assemble the phosphoxy-modified carbon felt adsorption electrode material in the capacitor deionization device, and apply an external electric field in the capacitor deionization device using a DC regulated power supply;
[0045] (3) Adjust the pH of the acidic leachate obtained in step (1) to 0.3-0.7, and then pass it into the capacitor deionization device for one adsorption. After the adsorption is completed, the solution is discharged to obtain the first adsorbed liquid. Then reverse the power supply and pass water in for one desorption. After the desorption is completed, the solution is discharged to obtain the first desorbed liquid. The first desorbed liquid is an indium nitrate solution.
[0046] (4) Adjust the pH of the first adsorbent obtained in step (3) to 0.8-1.2, and then pass it into the capacitor deionization device for secondary adsorption. After the adsorption is completed, the solution is discharged to obtain the second adsorbent. Then reverse the power supply and pass water in for secondary desorption. After the desorption is completed, the solution is discharged to obtain the second desorbent. The second desorbent is gallium nitrate solution.
[0047] The phosphoxy-modified carbon felt adsorption electrode material provided by this invention can be assembled into a capacitive deionization device. After passing through a solution, the direction of the applied electric field can be adjusted to achieve efficient adsorption-desorption, effectively avoiding the drawbacks of the traditional acid washing desorption method. It can achieve high adsorption capacity, high selectivity, and high cyclic separation and recovery.
[0048] Compared with existing technical solutions, the present invention has at least the following beneficial effects:
[0049] (1) Compared with existing adsorbent materials, the phosphoxy-modified carbon felt adsorption electrode material provided by this invention uses water as the desorbent instead of high-concentration acid, making the desorption method more environmentally friendly, avoiding damage to the adsorbent material, and exhibiting superior cycle performance. Under optimal conditions, it can complete 100 adsorption-desorption cycles when assembled in a capacitive deionization device, with the adsorption rate consistently remaining above 89%. Furthermore, the van der Waals forces formed by the applied electric field significantly enhance the reaction rate, achieving adsorption equilibrium for indium and gallium within 3 hours and 2.5 hours, respectively.
[0050] (2) Compared with existing electrochemical technologies, the phosphoxy-modified carbon felt adsorption electrode material provided by this invention has a rich pore structure and specific surface area that can significantly improve the adsorption capacity. Under optimal conditions, the saturated adsorption capacity for indium and gallium reaches 545.7 mg·g, respectively. -1 and 513.3 mg·g -1 Covalently grafted phosphoxy groups can achieve selective complexation of metal ions, with selective separation coefficients for indium and gallium reaching 62.69 and 73.56, respectively, under optimal conditions. The assembly and use of capacitor deionization devices are simpler, more efficient, and easier to control, making them particularly suitable for the efficient and high-purity separation and recovery of indium and gallium from acidic leachates of waste CIGS photovoltaic modules.
[0051] (3) Compared with existing adsorption electrode materials, the phosphoxy-modified carbon felt adsorption electrode material provided by the present invention utilizes dopamine self-polymerization reaction and Artherton Todd reaction to achieve mild chemical modification of the material. The preparation process is carried out in a normal temperature and pressure environment and does not use any toxic organic reagents, including binders. It is economical, green and safe. Attached Figure Description
[0052] Figure 1 This is an analysis chart of the saturated adsorption capacity of indium and gallium ions by the phosphoxy-modified carbon felt adsorption electrode material described in Example 1 of the present invention;
[0053] Figure 2 This is a graph showing the adsorption rates of various metal ions by the phosphoxy-modified carbon felt adsorption electrode material described in Example 1 of this invention.
[0054] Figure 3 This is a graph showing the recyclability analysis of the phosphoxy-modified carbon felt adsorption electrode material described in Example 1 of this invention;
[0055] Figure 4 This is a graph showing the recyclability analysis of the adsorption electrode material described in Comparative Example 1 of this invention;
[0056] Figure 5 This is a flowchart illustrating the use of the phosphoxy-modified carbon felt adsorption electrode material described in Embodiment 1 of the present invention for treating acidic leachate from waste copper indium gallium selenide photovoltaic modules. Detailed Implementation
[0057] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0058] In one specific embodiment, the present invention provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material, the method comprising the following steps:
[0059] (1) At room temperature, the mixed activated carbon (BJH desorption pore size is 2-50nm, BET specific surface area is 1000-1800m²) 2 / g, with a particle size range of 60-850μm), dopamine hydrochloride, a phosphine-containing substrate, tris(hydroxymethyl)aminomethane hydrochloride, and water, wherein the molar ratio of dopamine hydrochloride, the phosphine-containing substrate, tris(hydroxymethyl)aminomethane hydrochloride, and water is (0.1-1):(1-10):(0.1-1):300, and the ratio of dopamine hydrochloride to activated carbon is (0.1-1)mol:(100-1000)g, and the mixture is stirred at a speed of 50-200r / min for 1-2h at a temperature of 15-35℃, and then the pH is adjusted to 8-9 with sodium hydroxide to obtain a mixed dispersion;
[0060] (2) The carbon felt that has been ultrasonically cleaned and cut to a suitable size is immersed in the mixed dispersion obtained in step (1) at room temperature for 3-10 h at 20-30℃. The solid-liquid ratio of carbon felt to mixed dispersion is (0.2-1):1 g / mL. After the reaction is completed, phosphoxy-modified carbon felt adsorption electrode material is obtained.
[0061] It should be clarified that any use of the process provided in the embodiments of the present invention or any substitution or change of conventional data falls within the protection and disclosure scope of the present invention.
[0062] Example 1
[0063] This embodiment provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material, the method comprising the following steps:
[0064] (1) At room temperature, the mixed activated carbon (BJH has a desorption pore size of 2.5 nm and a BET specific surface area of 1700 m²) 2 The mixture consists of 500g of activated carbon, ethyl phenylphosphine, trimethylolaminomethane hydrochloride, and water, with a particle size range of 250-850μm. The molar ratio of dopamine hydrochloride, ethyl phenylphosphine, trimethylolaminomethane hydrochloride, and water is 0.7:5:0.6:300. The ratio of dopamine hydrochloride to activated carbon is 0.7mol:500g. The mixture is stirred at 100 r / min for 1.5h, and then the pH is adjusted to 8 with sodium hydroxide to obtain a mixed dispersion.
[0065] (2) At room temperature, the carbon felt that has been ultrasonically cleaned and cut to a size of 2.10m×2.10m is immersed in the mixed dispersion obtained in step (1) for 4 hours. The solid-liquid ratio of the carbon felt to the mixed dispersion is 0.5:1g / mL. After the reaction is completed, the solid and liquid are separated and dried to obtain the phosphoxy-modified carbon felt adsorption electrode material.
[0066] Example 2
[0067] This embodiment provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material, the method comprising the following steps:
[0068] (1) At room temperature, the mixed activated carbon (BJH has a desorption pore size of 2 nm and a BET specific surface area of 1500 m²) 2The mixture consists of: dopamine hydrochloride (particle size range 250-750 μm), diethyl phosphite, trimethylolaminomethane hydrochloride, and water, wherein the molar ratio of dopamine hydrochloride, diethyl phosphite, trimethylolaminomethane hydrochloride, and water is 0.1:2:0.6:300, and the ratio of dopamine hydrochloride to activated carbon is 0.1 mol:100 g. The mixture is stirred at 50 r / min for 1 h, and then the pH is adjusted to 9 with potassium hydroxide to obtain a mixed dispersion.
[0069] (2) At room temperature, the carbon felt that has been ultrasonically cleaned and cut to a size of 1.35m×1.35m is immersed in the mixed dispersion obtained in step (1) for 5 hours. The solid-liquid ratio of the carbon felt to the mixed dispersion is 0.2:1g / mL. After the reaction is completed, the solid and liquid are separated and dried to obtain the phosphoxy-modified carbon felt adsorption electrode material.
[0070] Example 3
[0071] This embodiment provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material, the method comprising the following steps:
[0072] (1) At room temperature, the mixed activated carbon (BJH has a desorption pore size of 20 nm and a BET specific surface area of 1800 m²) 2 The mixture consists of: dopamine hydrochloride (particle size range 300-650 μm), diisopropyl phosphite, tris(hydroxymethyl)aminomethane hydrochloride, and water, wherein the molar ratio of dopamine hydrochloride, diisopropyl phosphite, tris(hydroxymethyl)aminomethane hydrochloride, and water is 0.7:7:1:300, and the ratio of dopamine hydrochloride to activated carbon is 0.1 mol:100 g. The mixture is stirred at 100 r / min for 2 h, and then the pH is adjusted to 8 with sodium hydroxide to obtain a mixed dispersion.
[0073] (2) At room temperature, the carbon felt that has been ultrasonically cleaned and cut to a size of 2.85m×2.85m is immersed in the mixed dispersion obtained in step (1) for 3 hours. The solid-liquid ratio of the carbon felt to the mixed dispersion is 0.9:1g / mL. After the reaction is completed, the solid and liquid are separated and dried to obtain the phosphoxy-modified carbon felt adsorption electrode material.
[0074] Example 4
[0075] This embodiment provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material, the method comprising the following steps:
[0076] (1) At room temperature, the mixed activated carbon (BJH has a desorption pore size of 30 nm and a BET specific surface area of 1000 m²) 2The mixture consists of 600g of activated carbon, phenylphosphine, tris(hydroxymethyl)aminomethane hydrochloride, and water, with a particle size range of 250-850μm. The molar ratio of dopamine hydrochloride, phenylphosphine, tris(hydroxymethyl)aminomethane hydrochloride, and water is 0.1:1:0.6:300. The ratio of dopamine hydrochloride to activated carbon is 0.5mol:600g. The mixture is stirred at 100 r / min for 1 h, and then the pH is adjusted to 8 with sodium hydroxide to obtain a mixed dispersion.
[0077] (2) At room temperature, the carbon felt that has been ultrasonically cleaned and cut to a size of 3m×3m is immersed in the mixed dispersion obtained in step (1) for 3h reaction. The solid-liquid ratio of carbon felt to mixed dispersion is 1:1g / mL. After the reaction is completed, the solid and liquid are separated and dried to obtain phosphoxy-modified carbon felt adsorption electrode material.
[0078] Example 5
[0079] This embodiment provides a method for preparing a phosphono-modified carbon felt adsorption electrode material. The only difference between this method and Example 1 is that the molar ratio of dopamine hydrochloride, ethyl phenylphosphinate, tris(hydroxymethyl)aminomethane hydrochloride, and water is 0.1:5:0.6:300. All other aspects are the same as in Example 1.
[0080] Example 6
[0081] This embodiment provides a method for preparing a phosphono-modified carbon felt adsorption electrode material. The only difference between this method and Example 1 is that the molar ratio of dopamine hydrochloride, ethyl phenylphosphinate, tris(hydroxymethyl)aminomethane hydrochloride, and water is 1:1:0.6:300. All other aspects are the same as in Example 1.
[0082] Example 7
[0083] This embodiment provides a method for preparing a phosphono-modified carbon felt adsorption electrode material. The only difference between this method and Example 1 is that the molar ratio of dopamine hydrochloride, ethyl phenylphosphinate, tris(hydroxymethyl)aminomethane hydrochloride, and water is 0.1:5:0.1:300. All other aspects are the same as in Example 1.
[0084] Example 8
[0085] This embodiment provides a method for preparing a phosphono-modified carbon felt adsorption electrode material. The only difference between this method and Example 1 is that the molar ratio of dopamine hydrochloride, ethyl phenylphosphinate, tris(hydroxymethyl)aminomethane hydrochloride, and water is 0.1:5:0.1:300. All other aspects are the same as in Example 1.
[0086] Example 9
[0087] This embodiment provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material. The only difference between this method and Example 1 is that the ratio of dopamine hydrochloride to activated carbon is changed to 0.7 mol: 30 g, while the rest is the same as in Example 1.
[0088] Example 10
[0089] This embodiment provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material. The only difference between this method and Example 1 is that the ratio of dopamine hydrochloride to activated carbon is changed to 0.7 mol: 1500 g, while the rest is the same as in Example 1.
[0090] Comparative Example 1
[0091] This comparative example provides a method for preparing a phosphoxy-modified carbon felt adsorption electrode material. The only difference between this method and Example 1 is that activated carbon is not added to the mixed dispersion, and the amount of activated carbon reduced is increased proportionally to dopamine hydrochloride, phosphine-containing substrate, and tris(hydroxymethyl)aminomethane hydrochloride. All other aspects are the same as in Example 1.
[0092] Comparative Example 2
[0093] This comparative example provides an electrode material, which is the carbon felt material in Example 1.
[0094] Application Examples 1-3
[0095] Application Examples 1-3 provide an application of a phosphoxy-modified carbon felt adsorption electrode material. The phosphoxy-modified carbon felt adsorption electrode material used in Examples 1-3 is described below. The flowchart for treating acidic leachate from waste copper indium gallium selenide photovoltaic modules is shown below. Figure 5 As shown, it includes the following steps:
[0096] (1) After disassembling and crushing copper indium gallium selenide photovoltaic modules, they are leached with nitric acid to obtain an acidic leachate containing rare metals gallium and indium.
[0097] (2) Assemble the phosphoxy-modified carbon felt adsorption electrode material in the capacitor deionization device, and apply an external electric field in the capacitor deionization device using a DC regulated power supply;
[0098] (3) Adjust the pH of the acidic leachate obtained in step (1) to 0.5, and then pass it into a capacitor deionization device for one adsorption. After the adsorption is completed, drain the solution to obtain the first adsorbent solution. Then reverse the power supply and pass water in for one desorption. After the desorption is completed, drain the solution to obtain the first desorbent solution, which is an indium nitrate solution.
[0099] (4) Adjust the pH of the first adsorbent obtained in step (3) to 1.0, and then pass it into the capacitor deionization device for secondary adsorption. After the adsorption is completed, the solution is discharged to obtain the second adsorbent. Then reverse the power supply and pass water in for secondary desorption. After the desorption is completed, the solution is discharged to obtain the second desorbent. The second desorbent is gallium nitrate solution.
[0100] The contents of gallium ions and indium ions in the indium nitrate and gallium nitrate solutions obtained in the above application examples were determined, and the recovery rates of gallium and indium were calculated. The results are shown in Table 1. The formula for calculating the recovery rate is: Recovery rate = Mass of target element in the recovered nitrate solution / Mass of target element in acidic leachate × 100%.
[0101]
[0102] As can be seen from the data in Table 1, the phosphoxy-modified carbon felt adsorption electrode material provided by the present invention is used for selectively separating and recovering indium and gallium from the acidic leachate of waste copper indium gallium selenide photovoltaic modules. It has a high recovery rate and selectivity for indium and gallium, and can achieve efficient separation and high-purity recovery of indium and gallium.
[0103] Metal ion adsorption effect test:
[0104] The phosphoxy-modified carbon felt adsorption electrode materials obtained in Examples 1-10 and Comparative Examples 1-2 were assembled into a capacitive deionization device, and In-containing... 3+ Ga 3+ Al 3+ Zn 2+ Cd 2+ Cu 2+ Mg 2+ and Ni + A mixed metal solution (each metal ion concentration of 0.1 mmol / L) was prepared, and the pH values were adjusted to 0.5, 1, 1.5, 2, 2.5, 3, 3.5, and 4. The solution was then passed through a capacitive deionization device and circulated for 3 hours at 25°C. The concentrations of each metal ion in the mixed solution after the reaction were measured at different pH values, and the adsorption rates of the corresponding metal ions were calculated. When the pH value was 0.5, the adsorption rates and separation coefficients of indium in each example and comparative example are shown in Table 2. When the pH value was 1, the adsorption rates and separation coefficients of gallium in each example and comparative example are shown in Table 2.
[0105] The formula for calculating the adsorption rate is as follows: ,in:
[0106] —The initial concentration of metal ions in the solution (mg / L);
[0107] —The concentration (mg / L) of metal ions in solution when adsorption equilibrium is reached;
[0108]
[0109] —The initial concentration (mg / L) of metal ion A in the mixed metal solution;
[0110] —Equilibrium concentration (mg / L) of metal ion A in the mixed metal solution;
[0111] —Initial concentration (mg / L) of metal ion B in the mixed metal solution;
[0112] —Equilibrium concentration (mg / L) of metal ion B in mixed metal solution;
[0113] The formula for calculating the adsorption capacity qi is: ,in:
[0114] —The initial concentration of metal ions in the solution (mg / L);
[0115] —The concentration (mg / L) of metal ions in solution when adsorption equilibrium is reached;
[0116] V – Volume of the solution (L);
[0117] W – Amount of adsorbent material added (g).
[0118] Taking Example 1 as an example, in the above metal ion adsorption effect test, the phosphoxy-modified carbon felt adsorption electrode material provided in Example 1 had a saturated adsorption capacity of 545.72 mg / g for indium ions under the conditions of 25℃ and pH=0.5. Figure 1 The separation coefficient for separating indium ions from other metal ions is: ( Figure 2 The phosphoxy-modified carbon felt adsorption electrode material provided in Example 1 showed a saturated adsorption capacity of 513.26 mg / g for gallium ions at 25°C and pH=1.0. Figure 1 The separation coefficient for separating gallium ions from other metal ions is: ( Figure 2 ).
[0119] Cyclic stability test:
[0120] Taking Example 1 as an example, the phosphoxy-modified carbon felt adsorption electrode material provided in Example 1 was assembled into a capacitive deionization device. An acidic leaching solution with pH 0.5 was introduced for a first adsorption. After adsorption, the solution was discharged to obtain the first adsorbent. Then, the power supply was reversed and water was introduced for a first desorption. After desorption, the solution was discharged to obtain the first desorbent (indium nitrate solution), completing one adsorption-desorption cycle for indium nitrate. Subsequently, the first adsorbent solution with pH 1.0 was introduced into the capacitive deionization device for a second adsorption. After adsorption, the solution was discharged to obtain the second adsorbent. Then, the power supply was reversed and water was introduced for a second desorption. After desorption, the solution was discharged to obtain the second desorbent (gallium nitrate solution), completing one adsorption-desorption cycle for gallium nitrate. Thus, the adsorption rate of metal ions under different cycle numbers was obtained as follows: Figure 3 As shown. From Figure 3 It can be seen that after 100 adsorption-desorption cycles, the phosphoxy-modified carbon felt adsorption electrode material for In 3+ and Ga 3+ The adsorption rates still reached 89% and 90% respectively, proving that the adsorbent material has excellent cycle stability.
[0121] The adsorption electrode material provided in Comparative Example 1 was assembled into a capacitive deionization device, and a cycle stability experiment for gallium nitrate was conducted under the same conditions. The results are as follows: Figure 4 As shown, after 50 adsorption-desorption cycles, the adsorption electrode material for Ga... 3+ The adsorption rate decreased to 91%. In comparison... Figure 3 It can be observed that the material preparation method in this patent has more stable recyclability.
[0122]
[0123] The following points can be observed from the data in Table 2:
[0124] (1) As can be seen from the data in Examples 1-8, the phosphoxy-modified carbon felt adsorption electrode material provided by the present invention can achieve an adsorption rate of over 72.51% for indium under optimal conditions, and the separation coefficient is [missing information]. It can reach a value of over 50.24, with an adsorption rate of over 83.24% for gallium and a separation coefficient of over 50.24%. It can reach 41.25 or higher.
[0125] (2) A comprehensive comparison of Example 1 and Examples 9-10 shows that too little activated carbon results in a small specific surface area and excessive dopamine deposition, leading to poor performance; too much activated carbon will mask the grafted phosphoxy functional groups, reducing the number of effective functional groups and increasing mass transfer resistance. (3) A comprehensive comparison of Example 1 and Comparative Examples 1-2 shows that without activated carbon, there are very few adsorption sites and the adsorption effect is very poor, but with the same phosphorus-containing substrate, the adsorption selectivity is still good; pure carbon felt has very poor adsorption effect and selectivity.
[0126] The present invention has been illustrated with the above embodiments to illustrate its detailed structural features. However, the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for the components used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a phosphoxy-modified carbon felt adsorption electrode material, characterized in that, The preparation method includes the following steps: (1) Activated carbon, dopamine hydrochloride, phosphine-containing substrate and tris(hydroxymethyl)aminomethane hydrochloride are dispersed in a solvent and the pH is adjusted to alkaline to obtain a mixed dispersion; (2) Immerse the carbon felt in the mixed dispersion obtained in step (1), and after the reaction is completed, obtain the phosphoxy-modified carbon felt adsorption electrode material.
2. The preparation method according to claim 1, characterized in that, The particle size range of the activated carbon is 60-850 μm; Preferably, the activated carbon has a BJH desorption pore size of 2-50 nm; Preferably, the activated carbon has a BET specific surface area of 1000-1800 m². 2 / g.
3. The preparation method according to claim 1 or 2, characterized in that, The phosphine-containing substrate includes any one or a combination of at least two of diethyl phosphite, diisopropyl phosphite, phenylphosphine acid, ethyl phenylphosphinate, or dimethylphosphine oxide.
4. The preparation method according to any one of claims 1 to 3, characterized in that, The solvent in step (1) includes water.
5. The preparation method according to claim 4, characterized in that, The molar ratio of dopamine hydrochloride, phosphine-containing substrate, tris(hydroxymethyl)aminomethane hydrochloride, and water is (0.1-1):(1-10):(0.1-1):300; Preferably, the ratio of dopamine hydrochloride to activated carbon is (0.1-1) mol: (100-1000) g; Preferably, the solid-liquid ratio of the carbon felt to the mixed dispersion in step (2) is (0.2-1):1g / mL.
6. The preparation method according to any one of claims 1 to 5, characterized in that, The dispersion process in step (1) includes stirring; Preferably, the stirring time is 1-2 hours; Preferably, the stirring speed is 50-200 r / min; Preferably, the pH adjustment includes using potassium hydroxide and / or sodium hydroxide; Preferably, the pH is adjusted to 8-9.
7. The preparation method according to any one of claims 1 to 6, characterized in that, The reaction time in step (2) is 3-10 hours, preferably 3-5 hours; Preferably, the reaction temperature in step (2) is 20-30℃.
8. A phosphoxy-modified carbon felt adsorption electrode material, characterized in that, The phosphoxy-modified carbon felt adsorption electrode material is prepared by the preparation method described in any one of claims 1 to 7; The phosphoxy-modified carbon felt adsorption electrode material includes a carbon felt and a functional coating wrapped on the carbon felt. The functional coating is grafted with phosphoxy functional groups.
9. The application of the phosphoxy-modified carbon felt adsorption electrode material as described in claim 8, characterized in that, The phosphoxy-modified carbon felt adsorption electrode material is used to assemble a capacitor deionization device, which can selectively separate and recover rare metal elements in a solution. The solution includes an acidic leachate from copper indium gallium selenide (CIGS) photovoltaic modules; The rare metal elements include indium and / or gallium.
10. The application according to claim 9, characterized in that, The process of separating and recovering rare metal elements from the solution includes the following steps: (1) After disassembling and crushing copper indium gallium selenide photovoltaic modules, they are leached with nitric acid to obtain an acidic leachate containing rare metals gallium and indium. (2) Assemble the phosphoxy-modified carbon felt adsorption electrode material in the capacitor deionization device, and apply an external electric field in the capacitor deionization device using a DC regulated power supply; (3) Adjust the pH of the acidic leachate obtained in step (1) to 0.3-0.7, and then pass it into the capacitor deionization device for one adsorption. After the adsorption is completed, the solution is discharged to obtain the first adsorbed liquid. Then reverse the power supply and pass water in for one desorption. After the desorption is completed, the solution is discharged to obtain the first desorbed liquid. The first desorbed liquid is an indium nitrate solution. (4) Adjust the pH of the first adsorbent obtained in step (3) to 0.8-1.2, and then pass it into the capacitor deionization device for secondary adsorption. After the adsorption is completed, the solution is discharged to obtain the second adsorbent. Then reverse the power supply and pass water in for secondary desorption. After the desorption is completed, the solution is discharged to obtain the second desorbent. The second desorbent is gallium nitrate solution.
Citation Information
Patent Citations
Method for treating heavy metal wastewater by using zinc modified biochar electrode material
CN118515345A
Shaddock peel activated carbon for capacitive deionization as well as preparation method and application of shaddock peel activated carbon
CN120247021A